1991
DOI: 10.1007/bf00235186
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic responses to nonhypotensive central hypovolaemia induced by lower body negative pressure in men and women

Abstract: Haemodynamic responses to low levels of lower body negative pressure (LBNP) were investigated in two groups of healthy, normotensive volunteers (8 men and 8 women) during two repeated experimental runs on two occasions, the latter determined by the different phases of the menstrual cycle in the women. The data consisted of systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean blood pressure (MBP), pulse rate (fc), forearm blood flow (FBF) and forearm vascular conductance (FC). The resting card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
3
9
1
Order By: Relevance
“…However, it is known that syncope is more common in warm environments when individuals are vasodilated, and it has been shown recently that orthostatic tolerance during whole body heating does vary with the phase of the menstrual cycle [28]. The present study confirms previous reports whereby the vascular responses, at least in response to orthostasis, are unaffected by phase of the menstrual cycle [38,30].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, it is known that syncope is more common in warm environments when individuals are vasodilated, and it has been shown recently that orthostatic tolerance during whole body heating does vary with the phase of the menstrual cycle [28]. The present study confirms previous reports whereby the vascular responses, at least in response to orthostasis, are unaffected by phase of the menstrual cycle [38,30].…”
Section: Discussionsupporting
confidence: 93%
“…The absence of any influence of the phase of the cycle on the reflex vascular responses, although unexpected in terms of the hormonal changes, is broadly in agreement with the findings of others, who observed no effect of phase of the menstrual cycle on the responses to lower body suction [21,28,38], to quiet standing [24] or to other physiological stimuli [2,5,34]. However, it is suggested that there are alterations in orthostatic tolerance associated with the menstrual cycle when additional vasodilator stress is applied, such as whole body heating [28].…”
Section: Discussionsupporting
confidence: 91%
“…We did not assess blood volume, but others have noted women to have lower absolute plasma [13] or blood [3] volumes. Physically smaller people typically have smaller blood volumes than larger people and, as in all similar studies [3,[7][8][9]15], the women in the present study were smaller than the men.…”
Section: Discussionmentioning
confidence: 97%
“…However, the gender differences in these orthostatic stressors are quite variable. Depending on the magnitude of a given level of absolute submaximal LBNP, women have demonstrated smaller [5,6], similar [4,10] or larger [6] total peripheral resistance; similar [4,8,13] or greater forearm vasoconstriction [3,10,11], and similar [4,13,15] or potentiated [3,5,6,10,12,15] chronotropic responses. The mechanisms underlying these differences remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation